Histopathological Study on Poultry Enteritis in Azerbaijan Province of Iran - Daryoush, Mohajeri; Yousef, Doustar; Mehrdad, Nazeri (International Journal of Poultry Science, 2011)
In this survey, for morphohistopathological study of the enteritis in fowls, 70 specimens of pathologic intestinal lesions were randomly collected from necropsied fowls with the signs of enteritis from different flocks at Tabriz poultry clinics in a course of 6 months. They subjected to detail morphological and histological studies. Epidemiologically, the prevalence of the various kinds of enteritis in association with age, strain and sex was evaluated. One-sample chi-square test, revealed that the highest rate of occurrence (78.57%), belonged to broilers (p<0.01). It was observed greatly in 4-6 weeks of age (p<0.01). Also, by chi- square test, a significant relation between the sex and age of affection confirmed (p<0.01), as in the males the most of affliction belonged to 4-6 weeks of age and in the females it was 1-3 weeks of age. Histopathologically, we found that the highest rates of enteritis, related to catarrhal, hemorrhagic and necrotic enteritis respectively (p<0.01). This investigation demonstrated that the strain of Ross was likely in high risk (p<0.05). The relation between the strains and the kinds of enteritis was not significant.